P257 Surgical and hospital admission in adults newly diagnosed with inflammatory bowel disease (IBD) in the biological era in Spain: Results of the nationwide EpidemIBD study of GETECCU. (16th January 2018) - Chaparro, M; Cabriada, J L; Casanova, M J; Ceballos, D; Esteve, M; Fernández, H; Barreiro-de Acosta, M; García-Sánchez, V; Ginard, D; Gomollón, F; Llorente Poyatos, R; Nos, P; et al.
Abstract: Background: Aims: i) To assess the frequency of surgery and hospital admission in an inception cohort of adults newly diagnosed with IBD; ii) to describe the characteristics and indications for surgical interventions; iii) and to know the causes for hospital admissions. Methods: Prospective and population-based nationwide study in Spain. Adult patients diagnosed with IBD -Crohn's disease (CD), ulcerative colitis (UC) or indeterminate colitis (IC)- during 2017 in the 17 Spanish regions has been included and followed-up for 12 months after diagnosis. Data were captured in a web-based database (AEG-REDCap). Results: Up to October 31st 2017, 2, 404 patients from 122 centres covering approximately 50% of the Spanish population have been included. Of them, 53% were males, with mean age 40 years. In total, 49% had UC, 46% CD, and 5% IC. About 15% of patients had a family history of IBD. In CD patients, 53% had ileal and 26% ileocolonic location, and 13% perianal disease; 8% of patients had stenosing and 7% fistulising behaviour at the time of diagnosis. In UC patients, 30% had extensive colitis and 36% left-sided colitis at diagnosis. Median follow-up was 6 months (range 0–10 months). Eighty-five patients (3.5%) underwent 107 surgical procedures. Median time to first surgery was 0 months (range 0–4 months). As regards the first surgical procedure, 67% were urgent and 60% entailed abdominal surgery (15.3% for stenosis, 13% for abdominal abscess and 22.4% for perforation). Rates of surgery were higher in CD than in UC (7 vs. 0.6%, p < 0.01). CD patients with inflammatory behaviour had lower rates of surgery than those with strictures or fistula (5%, 11%, and 25%, respectively, p < 0.01). Surgery was also more frequent among CD patients with perianal disease than in those without it (28 vs. 4.3%, p = 0.01). Other variables, such as family history of IBD, or smoking habit were not associated with the need for surgery. A total of 648 patients (27%) were admitted to hospital during follow-up (10% of them had more than 1 admission) with disease diagnosis as major driver (93%). Median time from diagnosis to admission was 0 months (range 0–9 months). Reasons for hospital admissions are summarised in Table 1. Conclusions: In this large nationwide inception cohort in the biological era, a substantial proportion of patients underwent surgery, which was urgent in over two thirds of cases, and CD with aggressive manifestations as the main drivers. One third of patients were hospitalised -most of them at disease diagnosis- in the first months of follow-up